Influence of gas flow direction on plasma propagation in a circularly bent flexible dielectric tube of different inner diameters - Asma Begum; Md Readul Mahmud (AIP Advances)
This study investigates the ignition of non-thermal atmospheric pressure plasma in a 110 cm long, flexible, circularly bent dielectric tube with inner diameters of 4, 8, and 10 mm. Helium feed gas was introduced at one end and exited from the other, with a high-voltage (HV) electrode positioned at the tube’s midpoint. Discharge expansion on both sides of the HV electrode was analyzed with the ground placed 50 cm away from the electrode. Image analysis revealed that the discharge originated from the tube’s inner surface, constricted along the length expanded on both sides of the HV electrode. The discharge length along the gas flow direction (GFD) exceeded that against the GFD. This was validated by generating plasma using two distinct power supplies. The plasma length increased with the applied voltage and decreased with the inner diameter. The electric force on plasma is dominant near the HV source, while gas dynamics are dominant far away from the HV source. The discharge current and plasma expansion velocity were nearly identical near the HV electrode but decreased at greater distances from the electrode on both sides. The plasma velocity initially increased and then decreased along the tube’s length. The total force and plasma velocity along the GFD were higher than those against it, resulting in a longer discharge along the GFD. For the power supply with a longer off voltage state, the plasma length decreased with the gas flow rate (GFR), while for the power supply with no off-voltage state, the plasma length increased with the GFR up to a certain flow velocity, attributed to the plasma relaxation time linked to the off-voltage duration.